Pengaruh Konten Youtube “Bang Tutorial” Terhadap Minat Belajar Mengedit Video Pada Mahasiswa Broadcast - Muhammad Alawi; Rosita Anggraini (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
YouTube is a social media that is widely enjoyed and has a variety of information, one of which, tutorial content that is quite loved by the Indonesian people.  One of the YouTube channels that package and display tutorial content is "Bang Tutorial". The purpose of this study is to determine the effect and magnitude of the influence of YouTube tutorial content "Bang Tutorial" on the interest in learning video editing on broadcast students in South Jakarta. The concepts used in this study are social media, social media content, tutorial content and learning interest. Tutorial content (Variable X) consists of audio visual, talent, graphic, and pacing dimensions. Meanwhile, interest in learning (Variable Y) is in the form of interest in learning, feelings of pleasure, attention to learning, and learning involvement. This research uses the positivism paradigm with a quantitative approach. The method used is survey and the type of research is explanatory. The research population was students majoring in broadcast at a campus located in South Jakarta. The number of samples obtained using Raosoft calculator software is 96 respondents. Purposive sampling is a sampling technique used, namely a sampling technique by selecting respondents based on certain considerations. Data collection techniques were carried out by observation, literature and online questionnaires with Likert scale measurements. The results showed that partially and simultaneously the YouTube content variable "Bang Tutorial" had a significant effect on the interest in learning video editing on broadcast students in South Jakarta.